La hacienda Chucarapi en el valle de Tambo: : familia, propiedad y extensión. Siglos XVI - XIX - Eguiluz Menéndez, Percy (2023)
This study on the Chucarapi hacienda in the Tambo valley focuses on three aspects: The family, the property and the extension; regarding the first one we will try to know the origin and possession of this hacienda in a family and its descendants since the XVI century; the second aspect refers specifically to four trunks of a single family descendants that had in property the Chucarapi hacienda, namely: the Peralta Cabeza de Vaca, the Fernández Maldonado and Peralta, Alvizuri Fernández Maldonado and López de Romaña and Alvizuri. The third aspect is based on the Chucarapi hacienda and its extension from its origin in the 16th century to the 20th century, its fragmentation by inheritance and its consolidation in the aforementioned family trunks.